Tax Intensity, Intellectual Capital, and Independent Commissioners on Sustainability Reporting Moderated by Company Size (in Non-Cyclicals Consumer Companies Listed on the IDX 2019-2023) - Putri Lindeawati; Januar Eky Pambudi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Sustainability reporting serves as a key indicator of a company's implementation of the triple bottom line concept (people, planet, profit). This study aims to examine the influence of tax intensity, intellectual capital, and independent commissioners on sustainability reporting, with firm size as a moderating variable, in consumer non-cyclical companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This sector was chosen due to its stability and critical role in providing essential goods and services, making social and environmental responsibility highly significant. A quantitative approach was employed using secondary data from 14 companies selected through purposive sampling. Data analysis was conducted using panel data regression with the help of EViews 12.0. The results indicate that tax intensity has a negative effect on sustainability reporting, while intellectual capital and independent commissioners have a positive effect. Firm size does not moderate the effect of tax intensity but does strengthen the influence of intellectual capital and independent commissioners on sustainability reporting. The study recommends that companies enhance the quality of their intellectual capital and the role of independent commissioners, as well as manage tax obligations strategically, in order to improve sustainability reporting performance and long-term reputation.